2009
DOI: 10.1007/s10597-009-9236-1
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Escape from Self and Interpersonal Relationship on the Pathological Use of Internet Games

Abstract: The purpose of the present study was to examine whether Baumeister's escape from self theory may account for the pathological use of Internet games among Korean adolescents. A sample of 1,136 junior high school students completed measures assessing Internet game addiction (IGA), real-ideal self discrepancy, escape from self, current mood, peer relationships, perceived parent-child relationship, and parental supervision. IGA was significantly correlated with all of these variables. Multiple regression analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
146
1
13

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 212 publications
(177 citation statements)
references
References 18 publications
9
146
1
13
Order By: Relevance
“…In addition, another study of Taiwanese adolescent and young adults reported online game addicts exhibited higher intrinsic motivation to play games rather than an extrinsic motivation compared to non-addicted adolescents (Wan & Chiou, 2007). Finally, escapism appeared as the most important factor predicting Internet gaming addiction (Kwon et al, 2011) and pathological gaming (Dongdong et al, 2011), followed by perceived parent hostility, real-ideal self-discrepancy, and parental supervision (Kwon et al, 2011), and actual-ideal self-discrepancy and depression (Dongdong et al, 2011).…”
Section: Online Gaming Addiction Based On the Criteria For Pathologicmentioning
confidence: 96%
See 3 more Smart Citations
“…In addition, another study of Taiwanese adolescent and young adults reported online game addicts exhibited higher intrinsic motivation to play games rather than an extrinsic motivation compared to non-addicted adolescents (Wan & Chiou, 2007). Finally, escapism appeared as the most important factor predicting Internet gaming addiction (Kwon et al, 2011) and pathological gaming (Dongdong et al, 2011), followed by perceived parent hostility, real-ideal self-discrepancy, and parental supervision (Kwon et al, 2011), and actual-ideal self-discrepancy and depression (Dongdong et al, 2011).…”
Section: Online Gaming Addiction Based On the Criteria For Pathologicmentioning
confidence: 96%
“…Based on the database literature search, 18 studies were identified that assessed online gaming addiction by means of using adapted diagnostic criteria for pathological gambling and impulse control disorders not otherwise specified (Chan & Rabinowitz, 2006;Dongdong, Liau & Khoo, 2011;Gentile, 2009;Gentile et al, 2011;Han et al, 2007Han et al, , 2009Kwon, Chung & Lee, 2011;Lemmens, Valkenburg & Peter, 2009, 2011a, 2011bRau, Peng & Yang, 2006;Thomas & Martin, 2010;van Rooij, Schoenmakers, van de Eijnden & van de Mheen, 2010;van Rooij, Schoenmakers, Vermulst, van de Eijnden & van de Mheen, 2011;Wan & Chiou, 2006a, 2006b, 2007.…”
Section: Online Gaming Addiction Based On the Criteria For Pathologicmentioning
confidence: 99%
See 2 more Smart Citations
“…They used the Internet for many hours per week, mostly utilized dysfunctional coping strategies and showed worse interpersonal relations than peers who do not show signs of problematic Internet use (2). Others have suggested that Internet addiction can be explained by a need to escape from oneself and that may account for the excessive playing of Internet games (3).…”
Section: Problem Definitionmentioning
confidence: 99%